Pemberdayaan Pokdakan Mina Usaha Rumbai Bukit dalam pengolahan mie kaya nutrisi untuk meningkatkan imunitas tubuh di masa pandemi - Dian Iriani; N Ira Sari; Bustari Hasan; Tjipto Leksono (Unri Conference Series: Community Engagement, 2020)
Pandemic in the form of Covid-19 is a new type of disease caused by SARS-CoV-2 virus or Corona virus which can cause health problems in the form of respiratory system disorders, starting from mild symptoms such as flu, to lung infections, such as pneumonia. To maintain body immunity against Covid 19, nutritious food ingredients in the form of catfish are needed. Catfish is a type of fish that has a high economic value, where apart from being easy to cultivate, this fish also contains very high nutrients, namely 17.63% protein, 1.07% ash, 2.23% fat (DW), 12.14%, fat (WW), moisture content 81.57%, 47.15% saturated fatty acids, MUFA 40.41%, PUFA 12.45%. Therefore, it is very good for consumption during a pandemic. However, not everyone likes to consume catfish fresh, so it is processed in the form of catfish noodles. To increase consumer preference for catfish noodles, natural dyes from spinach and carrots are added which will give green and orange colors and attract consumers, so that ultimately nutrient-rich noodles are produced. This activity was carried out with 10 participants by implementing health protocols that aim to provide insight and practical knowledge to community groups in Rumbai Bukit Village, Rumbai District about fish noodle processing techniques so that they can increase family income, especially during the pandemic. The enthusiasm of the participants was very high so that the activity went smoothly. From the post-test results, it was found that 100% of the participants had understood the diversification techniques of fishery product processing.